- #1

- 164

- 0

How to solve this?

ln ( ln ( ln ((e^x) +4)))=e

ln ( ln ( ln ((e^x) +4)))=e

- Thread starter frozen7
- Start date

- #1

- 164

- 0

How to solve this?

ln ( ln ( ln ((e^x) +4)))=e

ln ( ln ( ln ((e^x) +4)))=e

- #2

Tide

Science Advisor

Homework Helper

- 3,076

- 0

Hint: The exponential function is the inverse of the natural logarithm.

- #3

- 164

- 0

e^e = ln ( ln ( e^x +4))

e^e^e = ln (e^x +4)

e^e^e^e = e^x +4

x = 20

Is it correct? Or is there any others more easier way?

- #4

- 128

- 0

Correct. x = ln(e^e^e^e - 4) = 20.08553691561896frozen7 said:

e^e = ln ( ln ( e^x +4))

e^e^e = ln (e^x +4)

e^e^e^e = e^x +4

x = 20

Is it correct? Or is there any others more easier way?

- Last Post

- Replies
- 3

- Views
- 10K

- Last Post

- Replies
- 3

- Views
- 2K

- Last Post

- Replies
- 3

- Views
- 9K

- Last Post

- Replies
- 7

- Views
- 1K

- Last Post

- Replies
- 10

- Views
- 4K

- Last Post

- Replies
- 5

- Views
- 14K

- Last Post

- Replies
- 3

- Views
- 2K

- Last Post

- Replies
- 1

- Views
- 1K

- Replies
- 21

- Views
- 8K

- Last Post

- Replies
- 1

- Views
- 834